Assessing income tax structure through a comparative lens: Evidence from India and Afghanistan - Sarwari, Rohullah; Sekhon, Shailinder (The International tax journal, 2026)
Taxation is essential for the survival of a country and serves as a key instrument for the development of a nation’s economy. In general, taxation is separated into two basic categories: direct taxes and indirect taxes. Direct taxes are paid directly by individuals or companies to the government, whereas indirect taxes are collected through intermediaries. This research focuses on the direct taxation structures of two nations, India and Afghanistan. The major purpose of the study is to comparatively assess and analyze the tax structures of these two nations in order to find their similarities and differences. Although the two countries are not comparable in terms of their economic and political circumstances, a comparative assessment of their tax systems provides useful insights into their institutional frameworks and administrative procedures. The study adopts a thematic strategy to collect and analyze the relevant data. Four key themes were created to meet the aims of the research. The data reveal that India, with its progressive tax system, and Afghanistan, with its relatively flat tax structure, differ in numerous structural and administrative features of direct taxes.